A seat at the table: The effects of workers' representation on firm performance and jobs - Andrea Mina; Daniele Moschella; Julian Tiedtke (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
Institutions representing the workers' voice have long been a contentious topic in the economic literature. Against a backdrop of inconclusive evidence and limited use of credible identification strategies, we study the impact of the 2015 policy change that introduced mandatory board-level employee representation in firms with over 1,000 employees in France. Using rich linked employer-employee data and two empirical strategies-a difference-in-differences and a difference-in-discontinuity approach-we examine how the reform affected firms and workers. Our results show a positive impact on job quality, with no evidence of adverse effects on firm performance, and heterogeneous effects between manufacturing and service sectors.
Keywords: J31; J53; K31; 330; Workers' Voice; Employee Representation; Job Quality; Corporate Governance; Difference-in-Discontinuity Design